2015
DOI: 10.4028/www.scientific.net/amm.813-814.293
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effect of Process Control Parameters on Tool - Chip Interface Temperature during Hard Turning of AISI D3 Tool Steel in Dry Condition

Abstract: Hard turning is recent upcoming technology through which surface quality of machined components can be enhanced while comparing with the traditional grinding method. Since the absence of metal cutting fluids during this process, numerous harmful effects on shop floor operators and possible negative impacts on environment can be eliminated. Normally some of the vital machinability aspects such as surface integrity of machined parts has been influenced by magnitude of cutting temperature which evolved in metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In a study that set out to explore the impact of turning performance parameters while turning heat-treated D3 tool steel, various researchers have established an interrelationship between process parameters and process responses and also specified the range of process parameters to control tool wear along with other process outputs. The study has recounted that axial feed along with a depth of cut controls the heat developed on the tool’s surface, 8 while an ultimate cutting speed of 240 m/min was suggested to limit excessive wear on the TiN coated CBN tool insert. 9 In a minor study by taking advantage of CBN inserts in the course of turning of D3 tool steel, Bouchelaghem et al 10 have established an interrelationship between the rate of tool wear, the surface roughness of the machined, the magnitude of cutting forces, and temperature in the machining region.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that set out to explore the impact of turning performance parameters while turning heat-treated D3 tool steel, various researchers have established an interrelationship between process parameters and process responses and also specified the range of process parameters to control tool wear along with other process outputs. The study has recounted that axial feed along with a depth of cut controls the heat developed on the tool’s surface, 8 while an ultimate cutting speed of 240 m/min was suggested to limit excessive wear on the TiN coated CBN tool insert. 9 In a minor study by taking advantage of CBN inserts in the course of turning of D3 tool steel, Bouchelaghem et al 10 have established an interrelationship between the rate of tool wear, the surface roughness of the machined, the magnitude of cutting forces, and temperature in the machining region.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the authors have obtained an optimum set of cutting parameter level using sequential approximation optimization. One study by Venkatesh and Senthilvelan 22 examined the effect of machining process variables on the temperature generated at the cutting zone in dry machining of AISI D3 steel. The authors have reported that the axial feed has major control on surface finish followed by the depth of cut and cutting speed.…”
Section: Introductionmentioning
confidence: 99%